STUDY OF HORIZONTAL LIGHT PIPE WITH DYNAMIC REFLECTOR IN THE TROPICS - Livia Hariyanto; Feny Elsiana; Danny Santoso Mintorogo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2022)
Horizontal light pipe (HLP) is a sustainable strategy for improving daylighting quality in buildings. The reflector is one of the HLP elements that collect and direct the incoming light in the pipe. Several reflector studies of HLP systems have been carried out in the last three decades under specific sunlight conditions at certain altitudes and azimuths or static conditions. This study proposes a dynamic reflector model in response to the movement of the sun angle. This study aimed to examine the impact of the dynamic reflector tilt angle on improving the quality of light by adapting the sun angle. The method used is an experimental simulation using IESVE software. This research is located in Surabaya, with a tropics climate. The results showed that modifying the reflector to be dynamic could increase the illuminance levels up to 29.9%, daylight factor values ​​up to 29.2%, and uniformity ratio values ​​up to 33.3%.